Upcycling celebrations ebook A use-what-you-have guide to decorating, gift-giving & entertaining. - Seo, Danny (2012)
Danny Seo is America's leading lifestyle authority on modern, eco-friendly living. In his last book, Upcycling, Danny demonstrated how to create beautiful things with the stuff you already have. Now he returns with 100 more projects-this time focused specifically on parties and holidays. Whether you're making dramatic party favors for New Year's Eve, giving a unique birthday gift, creating paper lanterns for a summer BBQ, or planning the Thanksgiving table, Danny shows how you can transform the ordinary into striking one-of-a-kind objects that will make every occasion a little more festive.